Тugolbai Sydykbekov as a state-level personality (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article examines the work of the patriarch of Kyrgyz literature Tugolbay Sydykbekov. An attempt is made to analyze his life and work. In other words, in this article the author tries to reveal the most important idea of Tugolbay Sydykbekov, as we believe this idea was to convey to the Kyrgyz society that you need to respect your native language and tradition and build your own independent country.
Keywords: native language, literature, book, tradition, culture